Adverse Selection in Corporate Loan Markets - BEYHAGHI, MEHDI; FRACASSI, CESARE; WEITZNER, GREGORY (Journal of Finance, 2026)
ABSTRACT Theories of competition typically predict a positive relationship between market concentration and prices. However, in loan markets, adverse selection can reverse this relationship as riskier borrowers become more likely to receive funding. Using supervisory data, we show that interest rates, borrower risk, and lending volume are higher in markets with more banks. We also create a novel measure of markup that is orthogonal to borrower risk, and find that, consistent with adverse selection, markups are higher after repeated borrowing relationships. Finally, we use a shock to large banks' lending costs to provide further support for the adverse selection channel.